CLINICAL AND BIOLOGICAL CORRELATIONS BETWEEN METABOLIC SYNDROME AND OXIDATIVE STRESS IN THE ELDERLY - Irina Cotea; Cristina Gavrilescu; Irina Esanu; Cranguta Paraschiv; Paloma Manea; Dragos Munteanu; Rodica Ghiuru (Romanian Society of Oral Rehabilitation, 2013)
Introduction. The chronic oxidative stress (OS) increases the production of free radicals and leads to a proinflammatory systemic condition. This one triggers the development for metabolic syndrome (MS) which is expressed by the pathological features of the modern civilization diseases (overweight, obesity, hypertension, dyslipidemias, cardiovascular disease, stroke, type 2 diabetes, cancer). Free radicals are also considered today the main cause of aging, and their control is a necessary modern strategic link that may delay or slow the senescence process. Objective: We aimed to evaluate the level of the oxidative stress in a lot of patients with metabolic syndrome compared to that of a lot of healthy adults. Method and material. We have evaluated 3 groups of patients: a control group (M) consisting of 30 healthy adults (student volunteers), and 80 patients diagnosed and treated for metabolic syndrome, out of which group A (patients younger than 65) and group B (patients aged over 65). There were evaluated clinic and metabolic characteristics of the patients with metabolic syndrome; these were correlated with the level of antioxidant enzymes such as SOD (superoxide) and GPx (glutathione peroxidase), while the lipid peroxidation was monitored by quantifying MDA (malondialdehyde). Results: Elderly patients with metabolic syndrome summarize clinical and metabolic features of antioxidant defense depending on the degree of lipid peroxidation. Thus it was observed that the oxidative stress increases with age, demonstrated by an increased level of antioxidant enzymes compared with group M. There were no statistically significant differences between the two groups A and B concerning the high levels of OS. In exchange there was found a definite increase of lipid peroxidation in group B compared to group A, proved by a statistically significant increase of MDA in the former group. Conclusions: The oxidative stress intensifies with age. Each of the components of MS is correlated positively and independently with systemic OS. Metabolic syndrome correlates with increased oxidative stress, demonstrated by increased levels of antioxidant enzymes (SOD and GPx) compared to controls. In the elderly with MS there was proved a significant increase of MDA compared to group A as to control group, demonstrating that the increased degradation phenomena of lipid peroxidation plays an important part in the process of senescence and justifies the association of antioxidant therapies.